1995
DOI: 10.1172/jci118127
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a role for GTP in the potentiation of Ca(2+)-induced insulin secretion by glucose in intact rat islets.

Abstract: Glucose initiates insulin secretion by closing K +-ATP channels, leading to Ca2" influx (E1); it also potentiates Ca2+-induced secretion (E2) when the K+-ATP channel is kept open using diazoxide and depolarizing concentrations of K + are provided. To examine the roles of purine nucleotides in E2, we compared the effects of glucose to those of the mitochondrial fuel monomethylsuccinate. Either agonist could induce E2 accompanied by significant increases in ATP, ATP/ADP ratio, and GTP/GDP ratio; GTP increased si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 40 publications
7
35
1
Order By: Relevance
“…On average, GTP levels corresponded to about 20% of ATP levels. This compares well with a proportion of 23% in two recent studies (19,22) but is lower than the values of 33-38% of other reports (16,18). The present study confirms that glucose increases GTP levels and the GTP:GDP ratio in islets (16,18,19) and, contrary to a previous study (18), shows that this effect is concentration-dependent and of rapid onset and reversibility.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On average, GTP levels corresponded to about 20% of ATP levels. This compares well with a proportion of 23% in two recent studies (19,22) but is lower than the values of 33-38% of other reports (16,18). The present study confirms that glucose increases GTP levels and the GTP:GDP ratio in islets (16,18,19) and, contrary to a previous study (18), shows that this effect is concentration-dependent and of rapid onset and reversibility.…”
Section: Discussionsupporting
confidence: 81%
“…However, the reported changes were smaller (17)(18)(19) and slower (18) than those of adenine nucleotides. Moreover, they were generally observed at one single glucose concentration and, when evaluated further, no concentration dependence could be found (17,18).…”
mentioning
confidence: 74%
“…It had been suggested that fatty acid oxidation results in increased ATP production, which is thought to initiate the process of insulin secretion induced by glucose (Warnotte et al, 1994). However, the ATP-mediated hypothesis for nutrient stimulation of insulin secretion has sometimes been questioned (MacDonald, 1990), leading propositions for the existence of both ATPdependent and ATP-independent pathways for glucose induction of insulin secretion (Aizawa et al, 1994;Meredith et al, 1995). Signal-transduction process for the ATP-independent pathway may involve phospholipase C and PKC activation (Aizawa et al, 1994;Komatsu et al, 1997) (Fig.…”
Section: Fa Metabolism In B-cellsmentioning
confidence: 99%
“…In contrast to ATP, GTP is capable of initiating insulin exocytosis in a Ca 2ϩ -independent manner both in native (45,46) and in clonal ␤-cells (24,40,45). Thus, GTP is generated by glucose and also modulates exocytosis di- rectly, which qualifies it as a messenger molecule (47). Whether heterotrimeric G-proteins or the monomeric Gprotein Rab3 is the target for GTP remains to be established (24,48).…”
mentioning
confidence: 99%